Cardiac Surgery-Associated Acute Kidney Injury in Children after Cardiopulmonary Bypass - Dmitrii Balakhnin; Ilya Chermnykh; Artem Ivkin; Evgeny Grigoriev (MDPI AG, 2024)
Cardiac surgery-associated acute kidney injury (CSA-AKI) is a complication of cardiopulmonary bypass surgery that frequently occurs in children. The increased availability of pediatric cardiac surgery leads to yearly increases in congenital heart disease (CHD) procedures performed worldwide. The number of complications, including pediatric CSA-AKI, has also increased. Children with CSA-AKI have worse postoperative periods and require more complex post-op intensive care. Thus, the timely commencement of interventions to prevent and to treat kidney injury in CHD children are one of a leading goals of pediatric cardiac intensive care.